Kualitas Pelayanan Terhadap Kepuasan Masyarakat pada Kantor Kelurahan Paccerakkang Kota Makassar - Arwan Arwan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Arwan, 2024. The Effect of Service Quality on Community Satisfaction at the Paccerakkang Village Office, Makassar City. Thesis of the Management Science Study Program of STIM-LPI Makassar (supervised by Dr. Andi Hendra Syam, S.E., M.Si. and Rahmi Usman, S.S., M.Pd.)This study aims to determine the Effect of Service Quality on Community Satisfaction at the Paccerakkang Village Office, Makassar City. The method used in this study is a quantitative method with the number of respondents of 100 employees which is used as a sample with a sampling technique, namely probability or random sample with the slovin technique, where the data collection technique using questionnaires. The analysis used in this study is a Simple regression test. The results of this study partially showed that the training variable had a positive effect on employee performance with the T value calculated for the service quality variable was 12.278 while theT table with the level (ꭤ) = 0.05, N-K = 100-2 = 98 was 1.984. Based on the test criteria of theT count>Ttable, then Ha is accepted and Ho is rejected and the significance level is 0.000<0.05. Which means that partially the service quality variable has a significant effect on community satisfaction.